If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 4(2x + 13) = 16 Reorder the terms: -5 + 4(13 + 2x) = 16 -5 + (13 * 4 + 2x * 4) = 16 -5 + (52 + 8x) = 16 Combine like terms: -5 + 52 = 47 47 + 8x = 16 Solving 47 + 8x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-47' to each side of the equation. 47 + -47 + 8x = 16 + -47 Combine like terms: 47 + -47 = 0 0 + 8x = 16 + -47 8x = 16 + -47 Combine like terms: 16 + -47 = -31 8x = -31 Divide each side by '8'. x = -3.875 Simplifying x = -3.875
| 24+1.50m=3m | | 18x^2+9xy-20y^2=0 | | -9y-12=8-4y | | 3x+4=6x-8 | | 4x+7(-x+4)=13 | | 8-(3n-1)=5-4n | | (2r+6)/5=-4 | | y^3-7y^2+3y-21=0 | | 8=30 | | 2x-10=4x+30 | | 3x+5-7(x+1)=4x+3 | | 7h-4=12-3h | | -64=4x-2(-5x-10) | | (m-2)/9=3 | | -5v-10=-110 | | 1+8e-2e=22 | | 3=-1.5n | | 16d^2-14d-15=0 | | 2(6-x)=2x+6 | | 4(x)+10=38 | | 21-4h-13=37+13h | | 2x-6=6x-18 | | 2x-6(3x+2)=180 | | (t+8)/4=6 | | 8+4m=9m+-7 | | t/6=12 | | 7x-5-2x+10=90 | | -2x-3(-x+13)=-33 | | 6b-7=-139 | | 5x-6-x=4+x+5 | | x*3(x*8)=10 | | -2=2+5*2-2-6*2 |